2022
DOI: 10.1007/978-3-030-93780-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogames as Drivers for Blockchain Application Development

Abstract: In this chapter, we outline reasons why cryptogaming, like cryptocurrencies in general, is an area of special interest for blockchain research. We suggest that cryptogaming is a field that drives forward the development of blockchain applications. Games require continuous interest, added value through interaction, and sufficient content in order to stay viable as a business model. They therefore challenge the ways in which we commonly view blockchains as first and foremost trust technologies and sidesteps from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Detailed analyses are still quite rare, with Cryp-toKitties (Dapper Labs, 2017), one of the early adopters, having received the most attention (Serada, 2022). The existing studies have identified basic principles of blockchain-based games, their marketing, and their design (Harviainen, Serada, & Sihvonen, 2022), and have demonstrated their dependence on the volatile cryptofinancial markets (Serada, Sihvonen, & Harviainen, 2021). Analyses of blockchainbased games from a traditional play-theory perspective are rather non-existent.…”
mentioning
confidence: 99%
“…Detailed analyses are still quite rare, with Cryp-toKitties (Dapper Labs, 2017), one of the early adopters, having received the most attention (Serada, 2022). The existing studies have identified basic principles of blockchain-based games, their marketing, and their design (Harviainen, Serada, & Sihvonen, 2022), and have demonstrated their dependence on the volatile cryptofinancial markets (Serada, Sihvonen, & Harviainen, 2021). Analyses of blockchainbased games from a traditional play-theory perspective are rather non-existent.…”
mentioning
confidence: 99%